Synthesis of Fluorescent N,P doped Carbon Quantum Dots Based Test Strip for Onsite Detection of Tartrazine and Ascorbic Acid - Ruby, G.; Bhavani, P. (Asian Journal of Chemistry, 2026)
Tartrazine and ascorbic acid are the prevalent food additives whose excessive use may lead to health complications, including allergies, behavioural alterations and oxidative stress. Expeditious, economical and dependable detection technologies are crucial for ensuring food safety and safeguarding customers. In this work, nitrogen and phosphorus co-doped carbon quantum dots (N,P-CQDs) were easily synthesized in one step via hydrothermal treatment of citric acid and ammonium phosphate. The fluorescent N,P-CQDs were immobilized on Whatman filter paper to create portable test strips for detecting tartrazine and ascorbic acid. Fluorescence quenching under UV light, due to photoinduced electron transfer and complex formation, enabled sensitive, selective and rapid detection within 3 min. The strips are stable, reusable and user-friendly, offering a practical approach for on-site beverage screening without complex instruments.